To simplify the expression \( 40 \cdot 5^{-2} \cdot (-2)^{-3} \) using the properties of integer exponents:
- Convert negative exponents to positive:
- For \( 5^{-2} \), we can write it as \( \frac{1}{5^2} \).
- For \( (-2)^{-3} \), we can write it as \( \frac{1}{(-2)^3} \).
So, we rewrite the expression: \[ 40 \cdot \frac{1}{5^2} \cdot \frac{1}{(-2)^3} \]
- Calculate the powers:
- \( 5^2 = 25 \)
- \( (-2)^3 = -8 \)
Now we have: \[ 40 \cdot \frac{1}{25} \cdot \frac{1}{-8} \]
-
Combine the fractions: \[ = 40 \cdot \frac{1}{25 \cdot (-8)} = 40 \cdot \frac{1}{-200} = \frac{40}{-200} \]
-
Simplify the fraction: \(\frac{40}{-200} = \frac{40 \div 40}{-200 \div 40} = \frac{1}{-5} = -\frac{1}{5}\)
Thus, the simplified expression is: \[ \boxed{-\frac{1}{5}} \]